Dynamic contrast enhanced CT in nodule characterization: How we review and report. Issue 1 (December 2016) - Qureshi, Nagmi; Shah, Andrew; Eaton, Rosemary; Miles, Ken; Gilbert, Fiona
Abstract Incidental indeterminate solitary pulmonary nodules (SPN) that measure less than 3 cm in size are an increasingly common finding on computed tomography (CT) worldwide. Once identified there are a number of imaging strategies that can be performed to help with nodule characterization. These include interval CT, dynamic contrast enhanced computed tomography (DCE-CT), 18 F-fluorodeoxyglucose positron emission tomography-computed tomography (18 F-FDG-PET-CT). To date the most cost effective and efficient non-invasive test or combination of tests for optimal nodule characterization has yet to be determined. DCE-CT is a functional test that involves the acquisition of a dynamic series of images of a nodule before and following the administration of intravenous iodinated contrast medium. This article provides an overview of the current indications and limitations of DCE- CT in nodule characterization and a systematic approach to how to perform, analyse and interpret a DCE-CT scan.